Frequency‐selective rasorber with two low insertion loss transmission bands. Issue 2 (24th November 2019) - Guo, Min; Lin, Yi; Guo, Tiantian; Chen, Qiang; Zheng, Yuejun; Fu, Yunqi
Abstract: A frequency‐selective rasorber (FSR) with two low insertion loss transmission bands is proposed. The FSR is composed of the resistive sheet layer at the top and bandpass FSS layer at the bottom, and separated by air spacer. Full‐wave simulation results show that the FSR realize two transmission bands at frequencies 8.5 GHz and 10.8 GHz with 0.45 dB and 0.77 dB insertion loss. Meanwhile, the band with | S 11 | < −10 dB is over 4.2‐8.8 GHz and 9.2‐17.4 GHz. Compared with the reported FSR with two transmission bands, the proposed FSR in this article achieves two transmission bands with lower insertion loss and wide absorption band at high frequencies. To validate the performance of the proposed FSR, the samples are fabricated and measured, reasonable agreement between simulated and measured results is achieved.